Age Differences in Hazard Perception of Drivers: The Roles of Emotion - Huo, Faren; Gao, Ranran; Sun, Cong; Hou, Guanhua (Frontiers in Psychology, 2022)
With the increasingly powerful functions of vehicle-mounted entertainment facilities, people (especially young drivers) like to listen to music while driving to render different atmospheres and emotions. However, emotions are important factors affecting drivers' decisions, behavior and may reduce drivers’ hazard perception, even promote dangerous driving behaviors of drivers. The purpose of this study is to explore the young and elderly drivers in assessing the hazard perception difference under different emotional states. We conducted a 3×2 mixed experimental design with emotion as a within-participants variable and age as a between-participants factor. A sample of 14 young drivers(mean age = 22.21, SD = 1.05)and 13 elderly drivers (mean age = 54.08, SD = 2.72) completed the hazard perception self-assessment of road traffic warning signs under negative emotion, neutral emotion, and positive emotion, randomly. The results showed that the young had the highest self-assessment hazard perception under the negative emotion arousal condition, while the old had the highest self-assessment hazard perception under the positive emotion arousal condition. In addition, When both groups were in a positive arousal state, the older group perceived more hazards than the young group. The results could help designers create driving emotions suitable for different driver groups, thus improving their perception of hazards and reducing risky driving.